Hubungan Pola Asah dan Asih Dengan Kejadian Stunting pada Balita di Kelurahan Mulyorejo Surabaya - Muhammad Risqi Ihya Ramdhan; Salsabila Farahdea Nindyaningrum; Lailatul Muniroh (Universitas Airlangga, 2023)
Background: Stunting can occur due to several factors, one of which is not fulfilling the basic needs of toddlers (stimulation, love, and care). In addition to care pattern related to feeding, stimulation and love patterns to toddlers are sometimes not well noticed by parents. Good stimulation and love patterns will later reduce the risk of nutritional problems, including stunting. Objectives: This study aims to analyze the correlation between the pattern of stimulation and love given by mothers to children with the incidence of stunting in toddlers in the Mulyorejo village, Surabaya. Methods: This study used a cross sectional design with a sample of 72 children under five obtained by simple random sampling. Data retrieval comes from primary sources with interview methods using questionnaires and direct measurements. The data obtained were then analyzed using the Spearman correlation test Results: As a result, most of the stimulation and love patterns from mothers were in the good category and based on the analysis there was no significant relationship between the stimulation pattern (p=0.397) and love pattern (p=0.112) with the incidence of stunting. Conclusions: The stimulation and love patterns from mothers have no significant relationship with the incidence of stunting. Even thought, the role of parents, especially mothers, is expected to be able to provide basic needs related to a balanced pattern of stimulation and love in supporting the development and growth of children optimally.